Synthesis of Substituted Benzimidazoles and Imidazo[ 4,5-b ]pyridines Under Microwaveand Solvent-free Conditions - MONTAZERI, NASSER; RAD-MOGHADAM, KUROSH (Asian Journal of Chemistry, 2010)
A dean and facile synthesis of benzimidazoles and imidazo[4,5- b ]pyridines is achieved from cyclocondensation of 1,2-diaminoaromatics with o-esters catalyzed by SiO2/H2SO4 in dry and microwave conditions.